2021
DOI: 10.1111/jfbc.13638
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐enzyme hydrolysis for preparation of ACE‐inhibitory peptides from sesame seed protein: Optimization, separation, and identification

Abstract: To prepare and identify ACE-inhibitory peptides originated from sesame seed protein, peptides with strong ACE-inhibitory activities were obtained via the optimization of protease and hydrolysis conditions, and these peptides were purified and identified by membrane separation, gel filtration, and liquid chromatography-mass spectrometry. Results showed that the dual-enzyme comprised alcalase and trypsin with the enzyme activity ratio of 3:7 was suitable to produce ACE-inhibitory peptides. The highest ACE-inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
3
12
0
Order By: Relevance
“…While Leu specificity was described by the manufacturer, Glu specificity was not. Nevertheless, this is in line with previous reports on Alc specificity (Doucet et al, 2003; Lu et al, 2021). These inconsistencies highlight a crucial aspect for successful application of the presented methodology.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…While Leu specificity was described by the manufacturer, Glu specificity was not. Nevertheless, this is in line with previous reports on Alc specificity (Doucet et al, 2003; Lu et al, 2021). These inconsistencies highlight a crucial aspect for successful application of the presented methodology.…”
Section: Resultssupporting
confidence: 94%
“…* References: a (García- ), b (García-Moreno, Gregersen, et al, 2020, c (Yesiltas et al, 2021), andd (García-Moreno et al, 2021). ** End of protein sequence Alc has broad specificity and has been reported to cleave after a wide range of residues (Ala/Leu/Val/Phe/Tyr/Trp/Glu/Met/Ser/Lys) with varying claims throughout literature (Doucet, Otter, Gauthier, & Foegeding, 2003;Lei, Cui, Zhao, Sun-Waterhouse, & Zhao, 2014;Lu et al, 2021;Sbroggio, Montilha, Figueiredo, Georgetti, & Kurozawa, 2016). A similar lack of consensus for Neut specificity is also found, although varying reports on the broad specificity of Alc and Neut exist, an in silico analysis based on supplier specificity (Novozymes A/S) was performed.…”
Section: 1in Silico Analysis and Design Of A Targeted Hydrolysis Processmentioning
confidence: 99%
“…Thus, considering the production cost and e ciency, 2.5 h is selected as the central value of the time factor of the RSM. This conclusion was consistent with Xin Lu et al (Lu, 2021), who found that with the extension of time, the reaction becomes more and more su cient, and the ACE inhibition rate increases gradually, but the long-term enzymatic hydrolysis will hydrolyze the polypeptide into amino acids without ACE inhibition activity.…”
Section: Single Factor Test Of Alkaline Proteasesupporting
confidence: 90%
“…The ACE‐inhibitory activity of LPC and LPH samples was measured using the HPLC hippuryl‐His‐Leu (HHL) substrate method described by Lu et al. (2021). The hippuric acid liberation amount from HHL was determined during the 30 min incubation at 37℃ with angiotensin I‐converting enzyme (from rabbit lung) in the presence (main sample) and absence (control) of LPC or LPH samples.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Alcalase as an endopeptidase cleaves the peptide bonds from the interior section of protein while the Flavourzyme as an endopeptidase and exopeptidase can break down the protein from interior and exterior (Xu, Galanopoulos, et al., 2020). Sequentially applying these enzymes or dual‐hydrolysis can produce peptides with higher DH or lower MWs and subsequently, amino acid composition and ACE‐inhibitory activity are altered (Lu et al., 2021). Sequential hydrolysis also has improved the bitterness of produced peptides from single hydrolysis.…”
Section: Introductionmentioning
confidence: 99%